An assistive tool in determining problematic internet use: validity and reliability of the “online cognition scale” in a sample of university students - Keser Özcan, Neslihan; Buzlu, Sevim (Journal of Dependence, 2005)
Objective: This study attempts to examine the validity and reliability of the Online Cognition Scale-OCS, an assistive tool developed by Davis in 2002 for determining the problematic Internet use, in a sample of university students.Method: The research was planned according to the methodological research method. 148 university students who used the Internet at least for 2 hours a week participated in the research on a voluntary basis. 73% per cent of students (n=108) were female, 27% (n=40) were male, the average age of the group was 21.01 (SD=1.563). In the research, in addition to the Online Cognition Scale-OCS, Demographical Information Form, UCLA Loneliness Scale, Beck Depression Scale and Multi-Dimensionally Perceived Social Support Scale were used as tools for collecting data.Result: For the test-re-test reliability of the scale, the Pearson correlation ratio detected for the total scale points obtained from both applications was .90, the Pearson correlation ratio detected for the social comfort sub-groups obtained from the two applications was .87, .76 for the loneliness / depression group points, .89 for the diminished impulse control sub-group points and .85 for the distraction sub-group points (p
Keywords: Online Cognition Scale; problematic internet use; reliability and validity